2012
DOI: 10.1016/j.mric.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral MR Angiography

Abstract: Since the introduction of contrast-enhanced MR angiography (MRA), several different techniques for imaging the peripheral arteries have evolved. All of them provide good diagnostic image quality, whereas some older techniques suffer from drawbacks, such as long acquisition time, impaired image quality from venous enhancement, and limited spatial resolution. MRA provides the most comprehensive modality offering the ability to tailor the examination to the patient and the specific question to be answered. The dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…For patients with peripheral arterial occlusive disease (PAOD) contrast-enhanced MRA has become the most appropriate noninvasive diagnostic method of choice [16]. Systematic reviews have confirmed the high diagnostic accuracy of peripheral CE-MRA [5].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with peripheral arterial occlusive disease (PAOD) contrast-enhanced MRA has become the most appropriate noninvasive diagnostic method of choice [16]. Systematic reviews have confirmed the high diagnostic accuracy of peripheral CE-MRA [5].…”
Section: Discussionmentioning
confidence: 99%
“…3 A high-field magnetic resonance (MR) scanner (1.5T or 3T) with modern phasedarray receive coils is necessary to obtain images with high spatial resolution and high signal-tonoise ratio, while still covering the region of interest. Dedicated phased-array extremity or wrist coils should be used whenever possible, depending on the region of interest and required coverage.…”
Section: Mra Techniquesmentioning
confidence: 99%
“…3 CE-MRA relies on the T1 shortening effect of paramagnetic GBCAs. This results in a significant difference in signal intensity between blood and adjacent tissue when using heavily T1-weighted arterial-phase imaging.…”
Section: Contrast-enhanced Mra Techniquesmentioning
confidence: 99%
See 2 more Smart Citations